The exposure-outcome relationship between physical and psychosocial factors and non-specific back pain in adolescents: a systematic review and meta-analysis protocol - Oka, Gauri A.; Ranade, Ashish S.; Deshmukh, Rupeshkumar B.; Shinde, Mayur K.; Pore, Prasad D. (Frontiers in Pediatrics, 2026)
BackgroundNon-specific back pain in adolescents is widely prevalent, with potential for chronicity in adulthood. Evidence points to various physical and psychosocial exposures of non-specific back pain in adolescents. Reviewing and synthesizing this evidence will help identify modifiable and non-modifiable exposures that can inform appropriate interventions. This systematic review and meta-analysis aims to estimate the global pooled prevalence of back pain in the age group of 10–19 years and describe the exposure-outcome relationships between various risk factors and non-specific back pain. We also aim to establish the dose-response relationship, if possible, between factors such as screen time exposure, BMI, psychological assessment scores, and non-specific back pain.MethodsA robust search strategy will be employed to search PubMed, PMC, and Scopus databases for articles in English. Observational studies that estimate the prevalence and severity of non-specific back pain in adolescents (age 10–19 years) will be included. Studies that have looked at exposures such as, but not limited to, the mode of transport to school, school bag weight, BMI, screen time exposure duration, physical activity, participants’ perceptions, and psychological, familial, and social factors will be eligible. Two authors will independently screen articles for suitability using the Rayyan software, extract data using the Review Manager 5 software, and assess the risk of bias using the JBI tool for critical appraisal of observational studies. The global pooled prevalence will be calculated using the Freeman-Tukey transformed proportions in the common effect inverse variance model. In case of low heterogeneity (I2 < 50%), the fixed effect model will be used, and a random effects model, otherwise. Subgroup analyses will be employed for socioeconomic strata, geography, use of school bags, type of school, screen time exposure, frequency and duration of physical activity, and objective assessments on psychosocial evaluation. If data are available, dose-response relationships will be determined between school bag weight, screen time duration, and severity of back pain.DiscussionIdentifying modifiable exposures of non-specific back pain can inform intervention strategies suitable for the individual or school setting. Systematic review registrationPROSPERO CRD42024572590.